Applicability Domains and Consistent Structure Generation. Issue 1 (25th May 2016) - Kaneko, Hiromasa; Funatsu, Kimito
Abstract: In de novo molecular design, quantitative structure‐activity relationship (QSAR) and quantitative structure‐property relationship (QSPR) models are important to estimate activity and property values, respectively, for virtual molecular structures. To operate QSAR and QSPR models appropriately, applicability domains (ADs) of the models must be defined because estimated values are unreliable for virtual molecular structures that are dissimilar to structures of training compounds. We describe several methods to construct AD models, and then introduce a structure generator to change molecular structures that exist outside ADs to conform to ADs. Abstract :